ANALISIS PENGARUH PENGHARGAAN TERHADAP RETENSI KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Gelawa Food Family Kabupaten Demak) - Mafaza Zulkurnain Ilyasa; Ismi Darmastuti (Diponegoro Journal of Management, 2022)
This study aims to determine and analyze the effect of the award variable on employee retention where organizational citizenship behavior (OCB) as an intervening variable, studies on employees of the Gelawa Food Family, Demak Regency. The population used is the employees of the Gelawa Food Family, Demak Regency. The number of samples used in this study were 38 people, using a sample collection technique, namely the Census technique. The research data was obtained through data collection with a questionnaire technique using a 1-4 scale like Likert. The scales used in this study include the Employee Retention Scale, Reward Scale and OCB Scale. The hypotheses proposed by the research are three hypotheses, where the research hypotheses will be proven by testing with quantitative methods using the quantitative method of Structural Equation Modeling (SEM) which is run with the SmartPLS software application and descriptive testing of the index value of each variable using Microsoft Excel 2013.Based on the SEM test, the model form of employee retention research can be explained well by the reward (R-Square = 0.887) and OCB (RSquare = 0.740). Based on the Q-Square calculation, it can be seen that reward and OCB variable have a good predictive level on the employee retention (Q¬Square = 0.904). The results of the path analysis test show that rewards have a very significant positive effect on employee retention (Tcount = 4.259; p = 0.000) and OCB (Tcount t = 14,275; p = 0.000), and OCB has a significant positive effect on employee retention (Tcount = 2,000; p = 0.046). The effect of rewards on employee retention mediated by OCB is 0.277. Based on the results above, it is known that the three research hypotheses are accepted